Response of polyisoprenoid concentration and profile in three groups of mangrove seedlings of coping with long-term salinity - MOHAMMAD BASYUNI; HIROSHI SAGAMI; SHIGEYUKI BABA; HIROSUKE OKU (Biodiversitas Journal of Biological Diversity, 2019)
Basyuni M, Sagami H, Baba S, Oku H. 2019. Response of polyisoprenoid concentration and profile in three groups of mangrove seedlings of coping with long-term salinity. Biodiversitas 20: 320-326. The response of polyisoprenoid (polyprenol and dolichol) concentration and distribution was investigated with three groups mechanism of coping with salinity: a secreting mangrove species of Avicennia officinalis, a non-secreting species (excluder) of Bruguiera cylindrica, and a salt-accumulating species of Xylocarpus granatum. The seedlings of three mangroves were grown under 0 and 3% salinity concentration for five months. Polyisoprenoids in the lipid extracts were examined by two-dimensional thin layer chromatography (2D-TLC). The pattern of the polyprenols and dolichols in the leaves and roots were categorized as two types (I and II). In category I, dolichols dominated over polyprenols, however, in category II, the existence of both polyprenols and dolichols was found. In the leaves, type-I was observed in A. officinalis under 0 and 3% salinity. On the other hand, type-II was found in B. cylindrica and X. granatum under 0 and 3% salt concentrations. A similar pattern was found in the roots, A. officinalis (type-I), and that in B. cylindrica and X. granatum was type-II. This finding depicted that the seedlings of A. officinalis, B. cylindrica, and X. granatum leaves and roots imply no change in the distribution type: the categories were distributed as type I or II under 0% salt concentrations, as well as type-I or II under 3% salt concentrations. This study implied that polyisoprenoids may play a protective function against salinity in the mangrove leaves and roots of three groups scheme (secreting, excluding, and accumulating) of salt management.